Diary of a Wimpy Kid: Old School - Book 10 - Kinney, Jeff (New York : Amulet Books, 2015)
"Life was better in the old days. Or was it? Thats the question Greg Heffley is asking as his town voluntarily unplugs and goes electronics-free. But modern life has its conveniences, and Greg isnt cut out for an old-fashioned world. With tension building inside and outside the Heffley home, will Greg find a way to survive?"--
When his town voluntarily unplugs and goes electronics- free, Greg misses the comforts and conveniences of modern life.
Keywords: Electronics -- Fiction; Family life -- Fiction; Diaries -- Fiction